Literasi Matematis Siswa Sekolah Dasar dalam Operasi Hitung Bilangan Ditinjau dari Self-Esteem - Alman, Alman; Ituga, Almuhaimin Sarnav (Paedagogie, 2025)
The importance of understanding the influence of self-esteem levels on students’ mathematical literacy lies in the fact that differences in self-confidence can affect the way students think, understand, and apply arithmetic operation concepts in problem-solving. This study aims to analyze elementary school students’ mathematical literacy skills on arithmetic operation material based on their levels of self-esteem—high, moderate, and low. The research employed a descriptive qualitative method involving 25 fifth-grade students from SD Negeri 20 Kota Baubau as the research subjects. The focus of the study was directed toward students’ ability to solve arithmetic operation problems by considering their respective levels of self-esteem. Data were collected through three main instruments: a questionnaire to measure self-esteem, a mathematical literacy test to assess students’ mathematical thinking skills, and interviews to obtain in-depth information about their thought processes and problem-solving strategies. The results of the study revealed variations in students’ mathematical literacy abilities influenced by their levels of self-esteem. Students with low self-esteem were generally unable to meet all indicators of mathematical literacy, those with moderate self-esteem demonstrated a fairly good understanding but faced difficulties in mathematical communication, while students with high self-esteem showed strong mastery of all mathematical literacy indicators.